PENGARUH MODEL NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN 01 NAN SABARIS - Dasmita Dasmita (Ensiklopedia of Journal, 2021)
This research is motivated by the low science learning outcomes of fourth grade students at SDN 01 Nan Sabaris, the problem was found based on the observations of students in grade IV, it appears that students have not been able to build their own knowledge and cannot communicate to their friends. This study aims to determine the effect of the Numbered Heads Together (NHT) model on the science learning outcomes of fourth grade students of SDN 01 Nan Sabaris. This type of research is Pre-Experimental. The design model in this research is Design Static Group Comparison. The research population was students in grades IV A and IV B at SDN 01 Nan Sabaris. Total sampling technique. The instrument used in this research is the dimension of knowledge. The data collection technique used is test results. Data analysis techniques by means of normality test, homogeneity test and hypothesis testing. Based on the results of the study, the average final test score for the experimental class was 76 and the average value obtained for the control class was 59. The results of the t-test analysis obtained the tcount value of 3.13, while the ttable value of 2.02, on dk (n1+n2 – 2) with a significant level of 0.05. It can be concluded that there is an effect of the Numbered Heads Together Model on science learning outcomes in class IV SDN 01 Nan Sabaris.